Road‐Level Charging Gaps and Infrastructure Enhancements in Japan's Electric Vehicle Transition - Xiaoyan Xu; Yoshikuni Yoshida; Jiawei Yong; Shintaro Fukushima; Renhe Jiang; Yin Long (Earth's Future)
Abstract The global transition to electric vehicles (EVs) is accelerating, yet inadequate charging infrastructure continues to impede adoption in certain regions. Japan, despite its early leadership in EV promotion and extensive patent portfolio, has been notably slow in transitioning, with charging accessibility emerging as a potential constraint. To address this challenge, we conduct a spatial evaluation of EV charger accessibility and assess strategies for optimizing network accessibility. Using data from 5,585 EV charging stations and road congestion patterns across the Tokyo metropolitan area, we developed a road‐level Charging Insufficiency Index to quantify accessibility gaps. Our results show that over 60% of roads in selected cities may face insufficient charging infrastructure, potentially posing barriers to EV adoption. Among the alleviation measures, expanding the rapid charging network achieves the greatest reduction in charging insufficiency, decreasing the total length of roads with above‐average charging insufficiency by approximately 904.10 km across 51% of cities during rush hour. This study offers a framework for guiding targeted infrastructure expansion and policy interventions, providing insights that can inform EV adoption strategies in Japan and other regions facing similar challenges.